Calculation of available water supply in crop root zone and the water balance of crops - HABERLE, Jan; SVOBODA, Pavel (Contributions to Geophysics and Geodesy, 2015)
Determination of the water supply available in soils for crops is important for both the calculation of water balance and the prediction of water stress. An approach to calculations of available water content in layers of the root zone, depletion of water during growth, and water balance, with limited access to data on farms, is presented. Soil water retention was calculated with simple pedotransfer functions from the texture of soil layers, root depth, and depletion function were derived from observed data; and the potential evapotranspiration was calculated from the temperature. A comparison of the calculated and experimental soil water contents showed a reasonable fit.